Complete Genome sequence of the nematicidal Bacillus thuringiensis MYBT18246 - Hollensteiner, J; Poehlein, A; Spröer, C; Bunk, B; Sheppard, AE; Rosentstiel, P; Schulenburg, H; Liesegang, H (BioMed Central, 2017)
Bacillus thuringiensisis a rod-shaped facultative anaerobic spore forming bacterium of the genus Bacillus. The defining feature of the species is the ability to produce parasporal crystal inclusion bodies, consisting of δ-endotoxins, encoded by cry-genes. Here we present the complete annotated genome sequence of the nematicidal B. thuringiensisstrain MYBT18246. The genome comprises one 5,867,749bp chromosome and 11 plasmids which vary in size from 6330bp to 150,790bp. The chromosome contains 6092 protein-coding and 150 RNA genes, including 36 rRNA genes. The plasmids encode 997 proteins and 4t-RNA's. Analysis of the genome revealed a large number of mobile elements involved in genome plasticity including 11 plasmids and 16 chromosomal prophages. Three different nematicidal toxin genes were identified and classified according to the Cry toxin naming committee as cry13Aa2, cry13Ba1, and cry13Ab1. Strikingly, these genes are located on the chromosome in close proximity to three separate prophages. Moreover, four putative toxin genes of different toxin classes were identified on the plasmids p120510 (Vip-like toxin), p120416 (Cry-like toxin) and p109822 (two Bin-like toxins). A comparative genome analysis of B. thuringiensisMYBT18246 with three closely related B. thuringiensisstrains enabled determination of the pan-genome of B. thuringiensisMYBT18246, revealing a large number of singletons, mostly represented by phage genes, morons and cryptic genes.